A survey of grade 10 learners in a high school in Gauteng South Africa and review of the HIV and sex education curriculum, as to its relevance to the learners declared needs - Whelan, Clive (Stellenbosch : Stellenbosch University, 2013)
Thesis (MPhil)--Stellenbosch University, 2013.